2019
DOI: 10.28991/cej-2019-03091329
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Supply Chain Capabilities on Logistic Efficiency for the Construction Projects

Abstract: Rapid technological advancements force organizations to be more proactive and efficient it operations while previous studies revealed that most of the public sector projects go over in term of time and cost. Although extensive literature is available but only for the private sector, the investigations on the public sector are scarce. After plentiful literature, it has found that timely and sage supply chain is a major hurdle. Various strategies and approaches have been proposed to tackle the situation but afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The study designs a questionnaire and distributes it among some a sample of population considered in this survey. The organizational justice scale is developed by Punniyamoorthy et al (2013) and Shahbaz et al (2019aShahbaz et al ( , 2019b. This questionnaire has been widely used to measure procedural justice, distributive justice and interactional justice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study designs a questionnaire and distributes it among some a sample of population considered in this survey. The organizational justice scale is developed by Punniyamoorthy et al (2013) and Shahbaz et al (2019aShahbaz et al ( , 2019b. This questionnaire has been widely used to measure procedural justice, distributive justice and interactional justice.…”
Section: Methodsmentioning
confidence: 99%
“…Fairness and impartiality towards all concerned are based on the principles of evenhanded dealing. Equity implies giving as much advantage, consideration, or latitude to one party as it is given to another (Shahbaz et al, 2019b). Along with economy, effectiveness, and efficiency, Equity is essential for ensuring that extent and costs of funds, goods and services are fairly divided among their recipients (Green Jr et al, 2012).…”
Section: Job Satisfactionmentioning
confidence: 99%
“…The construction industry is currently facing various challenges globally. It has been found that the Saudi Arabian construction industry finished only 30% of projects within the planned time and the average time consumed was between 10% to 30% [1]. Nigeria, Thailand, Hong Kong, and Ghana have also recorded similar observations [2].…”
Section: Introductionmentioning
confidence: 85%
“…The incapability to accomplish the disruptions in the supply chain and improper application of working mechanisms have negatively impact Malaysian projects as well [5]. Additionally, the unexpected acceleration in the prices of oil and the taxes has a significant effect on supply chain of Malaysian construction projects [1]. Construction industry's logic of collaboration can be observed by the parameter set by the team such as architects, managers, consultants and suppliers that contribute from the start of the projects till the end of the project [2].…”
Section: Malaysian Construction Industrymentioning
confidence: 99%
“…The optimal inventory levels and the reserve capacity production rate were derived. For other interesting literature, Shahbaz et al (2019) addressed the effect of the disruption problem on public sector construction projects. The disruption problem caused cost overruns and delays.…”
Section: Literature Reviewmentioning
confidence: 99%